GABPB1 activates transcription of ITPR3 and EMT in OSCC progression - Jun Liu; Chaoyue Zhao; Song Yang; Jichen Li (Functional & Integrative Genomics, 2026)

Digital twin-driven intelligent structural fault diagnosis and decision-making for earth-rock dams using large language models - Jichen Tian; Chen Chen; Yanling Li; Huibao Huang; Jiankang Chen (Engineering Structures, 2026)

Over-expression of PtCRK2 gene enhanced resistance of Pinus tabuliformis against Bursaphelenchus xylophilus - Mengjia Yang; Yuxi Chen; Mengtian Li; Xin Zhou; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Experimental study on flow and heat transfer characteristics of shark skin inspired heat exchange tubes and analysis of exergy and entransy properties - Jichen Sun; Hongguang Xiao; Xinwen Zhao; Wenzhen Chen; Kainan Jiang; Nan Zhang; Muzhen Li (Annals of Nuclear Energy, 2026)

Effects of poplar root aqueous extracts on tall fescue plants growth - Xiao Xu; Xiaoyu Li; Lei Wang; Longfeng Gong; Jichen Xu (Acta Physiologiae Plantarum, 2026)

Experimental and numerical investigation of offset and trajectory during descent of a shell–line–anchor single-point mooring system - Jichen Liu; Li Hu; Longming Chen; Zhenqing Wang; Yeqing Chen; Jiayang Li; Xin Bao (Ocean Engineering, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Equilibrium analysis of power battery sourcing strategies for competitive electric vehicle manufacturers under cap-and-trade - Haitao Chen; Jichen Li; Zhaohui Dong (Journal of Cleaner Production, 2026)

Fast solar-heating sponge with TEMPO-modified PDA coating for rapid recovery of highly-viscous oil on water - Jichen Huang; Xiaoyun Sun; Jinfeng Mei; Xudong Zheng; Zhongyu Li (Journal of Environmental Chemical Engineering, 2026)

Intermittent rivers in peri‑urban areas act as significant but overlooked sources of N2O emissions - Jiaao Bao; Junfeng Wang; Wenhao Xu; Zhuangzhuang Zhang; Thibault Datry; Lluís Gómez-Gener; Xin Chen; Jie Zhang; Jichen Li; William H. McDowell; Xinghui Xia (Water Research, 2026)

Nitrate modulates high CO2 effects on carbon partitioning in Gracilariopsis lemaneiformis: Trade-offs between particulate and dissolved organic carbon sequestration - Jichen Chen; Chi Song; Yicheng Ke; Mengmeng Wang; Jianing Qiu; Liujun Nie; Gang Li; Guang Gao (Environmental Research, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Improvement of near-infrared spectroscopic assessment methods for the quality of Keemun black tea: Utilizing transfer learning - Yurong Chen; Junhan Wang; Jingfei Shen; Yifan Zuo; Qianfeng Yang; Yongning Wei; Jichen Wang; Qing Yu; Wenjun Lv; Luqing Li (Food Research International, 2025)

MR2938 relieves DSS-induced colitis in mice through inhibiting NF-κB signaling and improving epithelial barrier - Ling Lv; Mireguli Maimaitiming; Shuli Xia; Jichen Yang; Tiantian Zhang; Yuming Wang; Xin Li; Iryna Pinchuk; Pingyuan Wang; Chang-Yun Wang; Zhiqing Liu (Marine Life Science & Technology, 2025)
Damage to the epithelial barrier is among key processes contributing to initiation and chronic inflammation in inflammatory bowel diseases (IBD). Only management therapy exists for IBD (e.g., anti-inflammatory and immunomodulatory agents, JAK/STAT inhibitors), and while novel therapeutic approaches have shown great potential, issues remain including route of administration, development of resistance to therapy and toxicity. Thus, novel small molecule inhibitors which can alleviate colonic inflammation and restore intestinal barrier functions are needed. Our previous study identified a new quinazolinone derivative MR2938, inspired by marine natural product penipanoid C, displaying impressive anti-inflammatory effects. In vivo efficacy study indicated that MR2938 had a dose-dependent effect on improving colitis symptoms, gut-barrier disruption, and colonic inflammation in an acute dextran sulfate sodium (DSS)-induced murine colitis as a model of epithelial injury relevant to IBD. Evaluation of potential mechanism involved in MR2938 efficacy demonstrated that MR2938 inhibited NF-κB-mediated inflammatory responses, and attenuated intestinal epithelial tight junction damage by restoring the expression of Occludin and ZO-1. Taken together, these data suggest that MR2938 is a promising lead compound for the treatment of IBD.

Estimating reference evapotranspiration using hybrid models optimized by bio-inspired algorithms combined with key meteorological factors - Hanmi Zhou; Linshuang Ma; Youzhen Xiang; Yumin Su; Jichen Li; Jiageng Chen; Sibo Lu; Cheng Chen; Qi Wu (Computers and Electronics in Agriculture, 2025)

Influence of PCHE size and types on thermodynamic and economic performance of supercritical carbon dioxide Brayton cycle for small modular reactors and its optimization - Chuntian Gao; Jichen Zou; Yunduo Ma; Weichao Li; Bowen Chen; Yandong Hou (Annals of Nuclear Energy, 2024)

Borehole lithology modelling with scarce labels by deep transductive learning - Jichen Wang; Jing Li; Kun Li; Zerui Li; Yu Kang; Ji Chang; Wenjun Lv (Computers & Geosciences, 2024)

Physical data-driven modeling of deformation mechanism constraints on earth-rock dams based on deep feature knowledge distillation and finite element method - Jichen Tian; Yonghua Luo; Xiang Lu; Yanling Li; Jiankang Chen (Engineering Structures, 2024)

Previously undescribed tetrahydroanthraquinones from Prismatomeris tetrandra (roxb.) K. Schum with antitumor cell proliferation activities - Xinyi Chen; Jichen Guan; Chen Zhang; Sizheng Li; Yingda Zang; Jiaqi Chen; Hongtao Jin; Fangfang Lai; Dongming Zhang (Phytochemistry, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

α2,3-Sialylation with Fucosylation Associated with More Severe Anti-MDA5 Positive Dermatomyositis Induced by Rapidly Progressive Interstitial Lung Disease - Rongrong Zhang; Li Guo; Jichen Sha; Shuwai Chang; Jiangfeng Zhao; Kaiwen Wang; Jiucun Wang; Jianxin Gu; Jing Liu; Shifang Ren (Phenomics, 2023)

miR-218-5p and miR-320a-5p as Biomarkers for Brain Disorders: Focus on the Major Depressive Disorder and Parkinson’s Disease - Zhirong Wan; Madiha Rasheed; Yumeng Li; Qin Li; Peifu Wang; Jilai Li; Zixuan Chen; Jichen Du; Yulin Deng (Molecular Neurobiology, 2023)

Studies on the inhibition of α-glucosidase by biflavonoids and their interaction mechanisms - Huan Li; Jichen Yang; Mengfan Wang; Xiangzhao Ma; Xin Peng (Food Chemistry, 2023)

Corrigendum: Effect of dietary soybean meal on growth performance, apparent digestibility, intestinal digestive enzyme activity and muscle growth-related gene expression of Litopenaeus vannamei - Kai Peng; Xiaoying Chen; Huijie Lu; Jichen Zhao; Yihong Chen; Chaozheng Li; Huo Li; Wen Huang (Frontiers in Marine Science, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Citrobacter portucalensis Sb-2 contains a metalloid resistance determinant transmitted by Citrobacter phage Chris1 - Yanshuang Yu; Zhenchen Xie; Jigang Yang; Ruixiang Yang; Yuanping Li; Yongguan Zhu; Yanlin Zhao; Qiue Yang; Jichen Chen; Hend A. Alwathnani; Renwei Feng; Christopher Rensing; et al. (Journal of Hazardous Materials, 2023)

A genetic linkage map of the Pacific white shrimp (Litopenaeus vannamei): QTL mapping for low-temperature tolerance and growth-related traits and identification of the candidate genes - Huijie Lu; Wei Chen; Fengkun Liu; Minwei Huang; Kai Peng; Jichen Zhao; Xiaoying Chen; Yuping Sun; Chaozheng Li; Yihong Chen; Zhenxing Liu; Huo Li; et al. (Aquaculture, 2023)

Laboratory study of Se speciation in the sediment and oligochaete Lumbriculus variegatus from an aquatic environment - Jichen Yang; Xin Yan; Hongsong Liu; Hongxing Chen; Wei Zhang; Wu Dong; Dan Li; Lingtian Xie (Environmental Science and Pollution Research, 2022)

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Effect of dietary soybean meal on growth performance, apparent digestibility, intestinal digestive enzyme activity and muscle growth-related gene expression of Litopenaeus vannamei - Kai Peng; Xiaoying Chen; Huijie Lu; Jichen Zhao; Yihong Chen; Chaozheng Li; Huo Li; Wen Huang (Frontiers in Marine Science, 2022)
Soybean meal is one of the major components of aquatic animal diets, whereas little information is available about the evaluation of soybean meal growth suppression mode of action. A 42-day feeding trial was performed to assess the effects of dietary soybean meal on growth performance, apparent digestibility, intestinal digestive enzyme activity, and muscle growth–related gene expression of Litopenaeus vannamei . A total of 600 shrimp were randomly distributed into 20 tanks with 30 shrimp per tank and four tanks per group. The soybean meal was added to the diets at the rate of 20% (T20), 28% (T28), 35% (T35), 42% (T42), and 50% (T50), respectively. Shrimp were fed with apparent satiation three times daily. Results indicated that the final body weight, weight gain rate, specific growth rate, feed intake, intestinesomatic index, dressed weight percentage, and the apparent digestibility coefficients of dry matter, crude protein, crude lipid, and ash were linearly decreased ( p < 0.05), but feed coefficient was linearly increased ( p < 0.05) as dietary soybean meal increased from 20% to 50%. The intestinal trypsin and amylase activities were decreased ( p < 0.05) as dietary soybean meal increased from 20% to 50%, and reached significance at the level of 35%, 42%, and 50%. Shrimp fed with T20 had higher ( p < 0.05) intestinal lipase activity than those fed with other diets. The mRNA relative expression of growth hormone, myogenic regulatory factor 5, and target of rapamycin was downregulated ( p < 0.05) as dietary soybean meal increased from 20% to 50%. To conclude, dietary soybean meal exceeded 28% significantly inhibited growth performance of L. vannamei , mainly due to the negative impact of soybean meal on digestion and feed utilization and also the inhibition on the muscle growth and related gene expressions.

Removal of COD in wastewater by magnetic coagulant prepared from modified fly ash - Wen Wang; Liqiang Qi; Pan Zhang; Jichen Luo; Jingxin Li (Environmental Science and Pollution Research, 2022)

Functional redundancy and specific taxa modulate the contribution of prokaryotic diversity and composition to multifunctionality - Yan Li; Yuan Ge; Jichen Wang; Congcong Shen; Jianlei Wang; Yong‐Jun Liu (Molecular Ecology, 2021)
Observational and experimental evidence has revealed the functional importance of microbial diversity. However, the effects of microbial diversity loss on ecosystem functions are not consistent across studies, which are probably tempered by microbial functional redundancy, specific taxa and functions evaluated. Here we conducted diversity manipulation experiments in two independent soils with distinct prokaryotic communities, and investigated how the initial community traits (e.g., distinct functional redundancy and taxonomic composition) modulate the contribution of prokaryotic diversity loss and composition shift to eight ecosystem functions related to soil nutrient cycling. We found that diversity loss impaired three functions (potential nitrification rate, N 2 ‐fixation activity and phosphatase) and multifunctionality only in the communities with low functional redundancy, but all examined functions were unaffected in the communities with high functional redundancy. All significantly affected functions belonged to specialized functions, while the broad function (soil basal respiration) was unaffected. Moreover, prokaryotic composition explained more functional variation than diversity, which was ascribed to the crucial role of specific taxa that influence particular functions. Taken together, this study provides empirical evidence for identifying the mechanism underlying the ecosystem response to changes in microbial community, with implications for improving the prediction of ecosystem process models and managing microbial communities to promote ecosystem services.

Negative effects of rare earth oxide nanoparticles of La2O3, Nd2O3, and Gd2O3 on the ammonia-oxidizing microorganisms - Yan Yue; Lin Qi; Yan Li; Jichen Wang; Congcong Shen; Yuan Ge (Journal of Soils and Sediments, 2020)

Transgenic creeping bentgrass plants expressing a Picea wilsonii dehydrin gene (PicW) demonstrate improved freezing tolerance - Hao Zhang; Yang Shi; Xinru Liu; Ruixue Wang; Jian Li; Jichen Xu (Molecular Biology Reports, 2018)

Do soil phytoliths accurately represent plant communities in a temperate region? A case study of Northeast China - Guizai Gao; Dongmei Jie; Yong Wang; Lidan Liu; Hongyan Liu; Dehui Li; Nannan Li; Jichen Shi; Chengcheng Leng (Vegetation History and Archaeobotany, 2018)

Response of ammonia-oxidizing betaproteobacteria to short-term fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Jiao Liu; Changfa Liu; Jin Li; Jichen Liu (Journal of Oceanology and Limnology, 2018)

Response of microbial biomass and bacterial community composition to fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Changfa Liu; Jiao Liu; Zhiping Yang; Jin Li; Jichen Liu (Acta Oceanologica Sinica, 2017)

Characterization of bacterial communities associating with larval development of Yesso Scallop (Patinopecten yessoensisis Jay, 1857) by high-throughput sequencing - Xueying Sun; Jichen Liu; Ming Li; Xuewei Zhao; Jun Liang; Pihai Sun; Yuexin Ma (Journal of Ocean University of China, 2016)

The expansin gene PttEXPA8 from poplar (Populus tomentosa) confers heat resistance in transgenic tobacco - Huabo Liu; Haoyang Li; Hao Zhang; Jian Li; Bingliang Xie; Jichen Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Microbial communities of an arable soil treated for 8 years with organic and inorganic fertilizers - Chen Chen; Jianan Zhang; Min Lu; Chun Qin; Yahua Chen; Li Yang; Qiwei Huang; Jichen Wang; Zhenguo Shen; Qirong Shen (Biology and Fertility of Soils, 2016)

Study on the New Methods of Ship Object Detection Based on GNSS Reflection - Yong Lu; Dongkai Yang; Weiqiang Li; Jichen Ding; Ziwei Li (Marine Geodesy, 2013)

Analysis of mutation in exon 17 of PTCH in patients with nevoid basal cell carcinoma syndrome - Jichen Li; Jinhui Wang; Yingqun Liu; Wei Wang (Molecular Biology Reports, 2010)

Functional analysis of the rice AP3 homologue OsMADS16 by RNA interference - Han Xiao; Yun Wang; Daofeng Liu; Wemming Wang; Xiaobing Li; Xianfeng Zhao; Jichen Xu; Wenxue Zhai; Lihuang Zhu (Plant Molecular Biology, 2003)